1994
DOI: 10.2172/49113
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic fabric filtration for simultaneous NO{sub x} and particulate control. Final report

Abstract: Corporation (OCF) for supporting the pilot-scale evaluation of the catalytic fabric filter concept. Also, the EERC would like to thank Raytheon Engineers & Constructors (RE&C) for their efforts in the completion of Task 4, Conceptual Design and Economic Evaluation, and their overall project technical support. The EERC Project Manager would like to specifically thank Ms. Felixa Eskey (DOE-PETC), Mr. Jack Pirkey (Con Edison), Dr. Aubrey Messing (ESEERCO), Ms. Debra DiMeo (ESEERCO), Dr. Patrick Aubourg (OCF), Ms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The views and opinions of authors expressed herein do not necessarily state or reflect those of the United States Government or any agency thereof. Bench-scale experimental results have shown that over 90% NO, removal can be achieved, the catalyst/fabric has promising self-abrasion characteristics, and the potential exists for substantially reduced cost when compared with conventional SCR/fabric filtration technology (6,7). However, development of the technology requires further evaluation of air-to-cloth ratio effects, ammonia slip, SO2 oxidation to S03, temperature cycling, catalyst-coated fabric preparation, fuel impacts, fabric cleaning (reverse-gas versus pulse-jet), catalyst life (poisoning and resistance to erosion), and filter performance/life (particulate control, differential pressure, and durability).…”
Section: Disclaimermentioning
confidence: 99%
“…The views and opinions of authors expressed herein do not necessarily state or reflect those of the United States Government or any agency thereof. Bench-scale experimental results have shown that over 90% NO, removal can be achieved, the catalyst/fabric has promising self-abrasion characteristics, and the potential exists for substantially reduced cost when compared with conventional SCR/fabric filtration technology (6,7). However, development of the technology requires further evaluation of air-to-cloth ratio effects, ammonia slip, SO2 oxidation to S03, temperature cycling, catalyst-coated fabric preparation, fuel impacts, fabric cleaning (reverse-gas versus pulse-jet), catalyst life (poisoning and resistance to erosion), and filter performance/life (particulate control, differential pressure, and durability).…”
Section: Disclaimermentioning
confidence: 99%
“…Bench-scale experimental results have shown that over 90% NO, removal can be achieved, that the catalyst/fabric has promising self-abrasion characteristics, and that the potential exists for substantially reduced cost compared to conventional SCR/fabric filtration technology (6,7). However, development of the technology requires further evaluation of air-to-cloth ratio effects, ammonia slip, SO2 oxidation to SO3, temperature cycling, catalyst-coated fabric preparation, fuel impacts, fabric cleaning (reverse.gas versus pulse-jet), catalyst life (poisoning and resistance to erosion), and filter performance/life (particulate control, differential pressure, and durability).…”
Section: List Of Tablesmentioning
confidence: 99%
“…Bench-scale experimental results to date have shown that over 90% NO, removal can be achieved, the catalyst/fabric has promising self-abrasion characteristics, and the potential eMsts for substantially reduced cost when compared with conventional SCR/fabric ftitration technology (6,7). However, development of the technology requires further evaluation of air-to-cloth ratio, ammonia slip, SO s oxidation to SOs, temperature cycling, catalyst-coated fabric preparation, fuel impacts, fabric cleaning (reverse-gas versus pulse-jet), catalyst life (poisoning and resistance to erosion), and filter performanceAife (particulate control, differential pressure, and durability).…”
Section: List Of Figuresmentioning
confidence: 99%